Meteorin-Like Ameliorates β Cell Function by Inhibiting β Cell Apoptosis of and Promoting β Cell Proliferation via Activating the WNT/β-Catenin Pathway - Hu, Wenchao; Wang, Rui; Sun, Bei (Frontiers in Pharmacology, 2021)
Meteorin-like (Metrnl) is a newly discovered myokine. Plasma Metrnl is decreased in subjects with newly diagnosed type 2 diabetes (T2D) and correlated with insulin resistance. This study aims to determine the effects of Metrnl on the apoptosis and proliferation of β cell. Mouse insulinoma MIN6 cells were divided into six groups: normal control, low glucose, high glucose, Vehicle, Metrnl, Dickkopf 1 (DKK1) groups. MIN6 cells in Metrnl group were transfected with recombinant pCDH-Metrnl vector. WNT/β-catenin pathway was inhibited using DKK1. Then the apoptosis of MIN6 cells was detected using flow cytometry and TUNEL labeling. Immunofluorescence of Ki67 was used to determine the β cell proliferation. db/db mice were confirmed as T2D group. Lentivirus-Metrnl was injected from the caudal vein of db/db mice once every two weeks for two times. High glucose induced the apoptosis of MIN6 cells and elevated expression of caspase 3. In addition, high glucose resulted in reduced β cell proliferation and cell viability, as well as decreased expression of β-catenin and TCF4. Metrnl ameliorated the above effects of high glucose. And the protecting role of Metrnl was inhibited by DKK1. T2D mice showed higher body weight and blood glucose compared with the controls. The β cell apoptosis was increased while the β cell proliferation and WNT/β-catenin pathway were inhibited in T2D mice. Metrnl treatment partly reversed the above changes in T2D mice. Metrnl ameliorates β cell function by inhibiting β cell apoptosis of and promoting β cell proliferation via activating the WNT/β-catenin pathway.